Bat Predation by Spiders - Nyffeler, Martin; Knörnschild, Mirjam (PLOS ONE, 2013)
In this paper more than 50 incidences of bats being captured by spiders are reviewed. Bat-catching spiders have been reported from virtually every continent with the exception of Antarctica (∼90% of the incidences occurring in the warmer areas of the globe between latitude 30° N and 30° S). Most reports refer to the Neotropics (42% of observed incidences), Asia (28.8%), and Australia-Papua New Guinea (13.5%). Bat-catching spiders belong to the mygalomorph family Theraphosidae and the araneomorph families Nephilidae, Araneidae, and Sparassidae. In addition to this, an attack attempt by a large araneomorph hunting spider of the family Pisauridae on an immature bat was witnessed. Eighty-eight percent of the reported incidences of bat catches were attributable to web-building spiders and 12% to hunting spiders. Large tropical orb-weavers of the genera Nephila and Eriophora in particular have been observed catching bats in their huge, strong orb-webs (of up to 1.5 m diameter). The majority of identifiable captured bats were small aerial insectivorous bats, belonging to the families Vespertilionidae (64%) and Emballonuridae (22%) and usually being among the most common bat species in their respective geographic area. While in some instances bats entangled in spider webs may have died of exhaustion, starvation, dehydration, and/or hyperthermia (i.e., non-predation death), there were numerous other instances where spiders were seen actively attacking, killing, and eating the captured bats (i.e., predation). This evidence suggests that spider predation on flying vertebrates is more widespread than previously assumed.